Penerapan Senam Kaki Diabetik terhadap Penurunan Kadar Gula Darah Penderita Diabetes Mellitus di Kecamatan Kartasura - Risha Yunni Margianti; Fida’ Husain (Journal of Educational Innovation and Public Health, 2024)
Background; The number of people with diabetes mellitus in the Sukoharjo Regency area is 17,184, while the number of people with diabetes mellitus in Kartasura District is 2142. Blood sugar levels are affected by diet, activity patterns, and medication adherence. Diabetic foot exercises are one of the efforts to lower blood sugar levels. When exercising, the muscles contract and relax. Sugar will be burned and converted into energy, so blood sugar will drop. The objectives of research; To find out the results of the implementation of diabetic foot exercises on the reduction of blood sugar levels in patients with diabetes mellitus. Method; This type of research is a case study that uses a descriptive research method. Foot exercises are done for 3 consecutive days, done once a day for 20 minutes. Result: The results of blood sugar levels before diabetic foot exercises were carried out in Mrs. F were 221 mg/dl and in Mrs. R were 158 mg/dl. The results of blood sugar levels after diabetic foot exercises were 175 mg/dl for Mrs. F and 138 mg/dl for Mrs. R. Summary: Foot exercises done for three days in a row can lower blood sugar levels.